2016
DOI: 10.1186/s40623-016-0585-z
|View full text |Cite
|
Sign up to set email alerts
|

An investigation into the remote triggering of the Oita earthquake by the 2016 Mw 7.0 Kumamoto earthquake using full wavefield simulation

Abstract: High-amplitude seismic waves from the Mw 7.0 Kumamoto earthquake of April 16, 2016, triggered another large earthquake 80 km to the NE roughly 30 s later. The source was located at shallow depths beneath the Yufuin geothermal field, Oita Prefecture, Japan, and the event magnitude was approximately 5.9. To date, this is one of the clearest known examples of a remotely triggered large earthquake. The triggered Oita event was followed by significant seismicity, which was distinct from the aftershocks of the Kumam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 27 publications
1
12
0
Order By: Relevance
“…3 lies a remarkably conductive zone. In this case, the static stress change (e.g., Hardebeck et al 1998) caused by the 2016 Kumamoto earthquake was not effectively transferred at distance, but instead, the dynamic effects of seismic shaking were considered to be reasonable earthquake triggers (Miyazawa 2016). Because Seis.…”
Section: Discussionmentioning
confidence: 99%
“…3 lies a remarkably conductive zone. In this case, the static stress change (e.g., Hardebeck et al 1998) caused by the 2016 Kumamoto earthquake was not effectively transferred at distance, but instead, the dynamic effects of seismic shaking were considered to be reasonable earthquake triggers (Miyazawa 2016). Because Seis.…”
Section: Discussionmentioning
confidence: 99%
“…Since Hill et al () first studied the dynamic earthquake triggering by the 1992 M 7.3 Landers earthquake, many such triggered events have been reported (e.g., Brodsky et al, ; Johnson & Bürgmann, ; Kilb et al, ; Miyazawa et al, ; Miyazawa, ; Parsons & Velasco, ; Richards‐Dinger et al, ; van der Elst & Brodsky, ; van der Elst et al, ; Yukutake et al, ). In one recent example, the 2016 M 7.3 Kumamoto earthquake triggered a M 5.7 event (semiofficial value, estimated by the Japan Meteorological Agency) during the passage of the seismic waves in the central part of Oita Prefecture, approximately 80 km from the mainshock (e.g., Miyazawa, , Uchida et al, , Yoshida, ). There have been relatively few reports of M > 5 earthquakes being remotely triggered during the passage of seismic waves from mainshocks (Lin, ; Pollitz et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Miyazawa 2011; Yukutake et al 2011) and the 2016 M7.3 Kumamoto earthquake (e.g. Enescu et al 2016;Miyazawa 2016). In both cases, seismicity activation has been observed predominantly at volcanoes, although there were cases of triggered events associated with active faults.…”
Section: Introductionmentioning
confidence: 99%
“…Uchide et al 2016;Yagi et al 2016). It is important to remark that Miyazawa (2016), Uchide et al (2016) and Yoshida (2016) demonstrated the dynamic triggering initiation (by main shock body or surface waves) of seismicity at the Yufuin-Beppu region, where a M5.9 occurred at very short times after the main shock. The aftershock area following the 2016 M7.3 Kumamoto earthquake can be divided into three subareas, as shown in Fig.…”
Section: Relatively Short Durations and Fast Decay Of Aftershocks At mentioning
confidence: 99%